Low- level laser: cost of therapy fornipple trauma - Danielly Negrão Guassú Nogueira; Franciane Maria da Silva Curan; Alexandrina Aparecida Maciel Cardelli; Rosângela Aparecida Pimenta Ferrari; Tatiane Tokushima; Rodrigo Antônio Carvalho Andraus
Abstract Objectives: to measure the micro-cost of local laser therapy (LL) and transcutaneous laser therapy application by Irradiation Laser Intravascular of Blood (ILIB) to treat nipple trauma and compare the most effective and efficient alternative treatment. Methods: a cross-sectional analytical and quantitative study with analysis on the micro absorption cost, implemented as a clipping, from a randomized clinical trial that used two types of laser therapy to treat nipple trauma due to breastfeeding. The sample consisted of 101 nipple lesions. Patients were randomized into three groups (Control - CG, Local Laser -LLG and ILIB-ILIBG). Materials used, direct labor (DL) and laser equipment were predictors of costs. The delta calculation (effect size) was the indicator for measuring effectiveness and efficiency. Results: after three sessions, the average final cost was R$ 40.04for CG, R$ 53.55for LLG and R$ 67.29for ILIBG. After three sessions of treatment, ILIBG showed a great reduction in the lesion area, but with a higher cost (p<0.05). Conclusions: ILIBG had a better effect on healing the nipple trauma when compared to CG and LLG, even though it is more expensive, it suggests a positive cost-benefit and the most effective and efficient alternative treatment.